USABILITAS GOOGLE CLASSROOM MENGGUNAKAN USE QUESTIONNAIRE DALAM DISKUSI INTERAKTIF PERKULIAHAN DI MASA PANDEMI - Muhammad Thohir; Nur Rakhmad Diana; M. Affan Al Habsyi; Susilowati Susilowati (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
The development of technology and the presence of the Covid-19 outbreak has made the world of education have no ideal choice except for distance learning. This encourages the use of various internet-based Learning Management System (LMS) supporting applications. Google Classroom is one of the most commonly used media. This study aims to find out the usability of Google Classroom to the students along their online-learning. The sample of this research was 105 students of Islamic Educational Study Program which selected by using purposive sampling. This research use survey research method. The result of this research shown that the usability of Google Classroom concluded as a high level, states as 80% of (usefulness), moreover there were as much as 80% students experienced that Google Classroom is easy to use, and there were also easy to access the learning material shown by 83% students. Additionally, the students also feel satisfy using Google Classroom as the media of interactive discussion, proved by the percentage of satisfaction of 79%.